2021
DOI: 10.1021/acs.accounts.1c00479
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphinamide-Based Catalysts: Discovery, Methodology Development, and Applications in Natural Product Synthesis

Abstract: work describes the development of the method for synthesizing P-stereogenic phosphinamides via desymmetric enantioselective C−H arylation.• Qin, X.-L.; Li, A.; Han, F.-S. Desymmetric enantioselective reduction of cyclic 1,3-diketones catalyzed by a recyclable P-chiral phosphinamide organocatalyst. J. Am. Chem. Soc. 2021, 143, 2994 This work describes the application of the P-stereogenic phosphinamides as organocatalysts in desymmetric enantioselective reduction of cyclic 1,3-diketones and the mechanistic study. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Admittedly, the desymmetric enantioselective reduction of cyclic 1,3-diketones has been widely investigated, including CBS, enzyme, and transition-metal-catalyzed reductions . We demonstrated that the P -stereogenic phosphinamide catalysts exhibit several important advantages over the reported methods in terms of the overall catalytic efficiency, such as the broad substrate compatibility, high stereo- and diastereoselectivity, the convenience of scale up and operation, and most significantly the ease of structural diversification as well as good the stability and recyclability of catalysts. , …”
Section: Results and Discussionmentioning
confidence: 95%
“…Admittedly, the desymmetric enantioselective reduction of cyclic 1,3-diketones has been widely investigated, including CBS, enzyme, and transition-metal-catalyzed reductions . We demonstrated that the P -stereogenic phosphinamide catalysts exhibit several important advantages over the reported methods in terms of the overall catalytic efficiency, such as the broad substrate compatibility, high stereo- and diastereoselectivity, the convenience of scale up and operation, and most significantly the ease of structural diversification as well as good the stability and recyclability of catalysts. , …”
Section: Results and Discussionmentioning
confidence: 95%
“…Erinacines are a branch of the cyathane diterpenoids incorporated with the featured 5-6-7 tricyclic carbocycle decorated with xylose on the cycloheptane moiety. 1 As selectively depicted in Fig. 1, with the exception of erinacine A ( 1 ), erinacines contain a trans -fused 6-7 ring system and 1,4- anti angular-methyl quaternary carbon centers.…”
mentioning
confidence: 98%
“…A multitude of innovative synthetic strategies for forging the 5-6-7 skeleton have been developed. 1,3 As selectively depicted in Fig. 2, Snider and co-workers 3 a reported the first total synthesis of (+)-erinacine A by taking advantage of palladium-catalyzed carbonylation of dienyl triflate and carbonyl ene reaction, constructing the 5-6-7 framework in seven steps (Fig.…”
mentioning
confidence: 99%
“…14 In addition, phosphinic amides serve as effective directing groups 15 or ligands 16 for transition-metal catalysis or are used as organocatalysts themselves. 17 Traditional methods for the synthesis of phosphinic amides 11 include the treatment of phosphinic halides with amines, 18 a two-step reaction of phosphine chloride with amines followed by oxidation, 19 and the condensation of phosphinic acids with amines under certain conditions. 20 A range of new methods for the construction of phosphinic amides have appeared in recent years.…”
mentioning
confidence: 99%
“…Phosphinic amides, with the structure R 2 P­(O)­NR 2 , are a type of important organophosphorus compound showing multifaceted properties, such as biological activity, light-emitting behavior, and flame-retardant property . In addition, phosphinic amides serve as effective directing groups or ligands for transition-metal catalysis or are used as organocatalysts themselves . Traditional methods for the synthesis of phosphinic amides include the treatment of phosphinic halides with amines, a two-step reaction of phosphine chloride with amines followed by oxidation, and the condensation of phosphinic acids with amines under certain conditions …”
mentioning
confidence: 99%